Effectiveness of foreign aid in poverty reduction in Africa: The role of fiscal policy - Onyebuchi Iwegbu; Risikat O. S. Dauda (CBN Journal of Applied Statistics, 2022)
This study examines foreign aid effectiveness in poverty reduction in Africa with focus on the role of regional fiscal policy on education and health. The study employs panel dynamic ordinary least squares (DOLS) estimation technique and covers the period 1980-2017. The results reveal that foreign aid augmented with effective fiscal policy on education significantly improves the income level in all the regions except Central Africa, and consumption in the Western and Central regions. When augmented with effective fiscal policy on health foreign aid enhances households' income in West and Central Africa and consumption in West and Southern regions. Furthermore, foreign aid augmented with effective fiscal policy in education (health) reduces poverty head- count in the West and Central (in all regions except Central) regions of Africa. The study concludes that foreign aid augmented with fiscal policy on education improves income in all regions except Central Africa; and West and East Africa when aug- mented with health expenditure. To sustain the effectiveness of foreign aid in Africa there is the need to improve governments' allocation to the health and education sectors to deepen households' income.
Keywords: F35; H51; H52; I32; 330; Education; foreign aid; government expenditure; health; panel dynamic ordinary least squares